Analisa Kinerja Asuransi Jiwa dalam Paradigma SCP - Garry Giovanno (Jurusan Ilmu Ekonomi Universitas Katolik Parahyangan, 2022)
The market structure in an industry will have an impact on the behavior of each company so that it will affect performance, which in turn can drive the wheels of the economy. The purpose of this study is to find out whether the SCP paradigm applies to the life insurance industry in Indonesia in 2014 - 2018. The data used in this study is panel data of 20 life insurance companies in Indonesia in period 2014 to 2018 which were estimated using Generalized Least Square (EGLS) errors. The results of this study indicate that the SCP paradigm does not apply to the Life Insurance Industry in 2014 - 2018.